Who chooses alternative sources of information about childhood vaccinations? A cross-sectional study - Bellomo, Rosa Katia; Cerabona, Vito; Massimi, Azzurra; Migliara, Giuseppe; Sparano, Michele; Novello, Francesco; Schilirò, Tiziana; Siliquini, Roberta; Villari, Paolo; De Vito, Corrado (Frontiers in Public Health, 2023)
Introduction: Vaccine hesitancy can lead to problematic outcomes in terms of public health. A factor playing a fundamental role in this dynamic is the source of information considered by parents in the decision-making progress that leads to the acceptance or refusal of childhood vaccinations. This study aims to investigate the sources of information considered by the parents of children attending primary and secondary schools in two large Italian cities and to identify predictors that led to choosing alternative sources of information. Methods: An online questionnaire was administered to the parents of students attending elementary, middle and high schools in Rome and Turin. Two validated tools were used: the Parent Attitudes about Childhood Vaccines Survey and the Vaccine Health Literacy of adults in Italian. Sources of information about vaccinations, trust towards the healthcare system, hesitancy and attitudes about COVID-19 vaccinations, were also investigated. A multivariable logistic regression model was built to identify predictors of the preferred sources of information on the topic. Results: Totally, 2301 answers to the survey were collected from June to October 2021. Of these, 1127 came from parents in Rome (49%) and 1174 from parents based in Turin (51%) with a mean age of 47.7 years (±6.4). The majority of the respondents were mothers (81%), married (73%), with two or more children (70,5%). The multivariable logistic regression model results showed that fathers were more inclined than mothers to use alternative sources of information (OR 1.48, 95% CI 1.29 – 2.00). Moreover, a higher level of vaccine hesitancy was a strong predictor for choosing alternative sources of information (OR 2.45, 95% CI 1.73 – 3.46). The HLVa-it scores show that parents with a lower Vaccine Literacy (VL) were more inclined to use alternative sources of information. Discussion: Addressing health literacy issues and changing the official forms of communication could help improving vaccine acceptance. This study shows the importance of rebuilding a trust relationship between patients and health care providers, which is fundamental in the fight against vaccine hesitancy.